Improving PLDA Speaker Verification using WMFD and Linear-weighted Approaches in Limited Microphone Data Conditions - Ahilan, K.; Dean, D.; Sridharan, S. (My University, 2015)
This paper proposes the addition of a weighted median Fisher discriminator (WMFD) projection prior to length-normalised Gaussian probabilistic linear discriminant analysis (GPLDA) modelling in order to compensate the additional session variation. In limited microphone data conditions, a linear-weighted approach is introduced to increase the influence of microphone speech dataset. The linear-weighted WMFD-projected GPLDA system shows improvements in EER and DCF values over the pooled LDA- and WMFD-projected GPLDA systems in interview- interview condition as WMFD projection extracts more speaker discriminant information with limited number of sessions/ speaker data, and linear-weighted GPLDA approach estimates reliable model parameters with limited microphone data. Index Terms: speaker verification, i-vectors, GPLDA,WMFD, linear-weighted